Konstruksi Kuasa dalam Praktik Jual Beli Tanah - Faradiba, Laetetia Sekar; Umar, H.; Putra, Akbar Kurnia (Wajah Hukum, 2025)
The purpose of this research is to analyze the use of power of attorney in land sale and purchase practices. According to KUHPerdata, Article 1792 of the Civil Code governs the delegation of power to sell in the context of real estate transactions in Indonesia. The transfer of land rights can only be executed by the actual owner, whereas this power of attorney is solely for management purposes. Several things can cause the power of attorney to be terminated, including the grantor's withdrawal, the grantee's or the grantor's bankruptcy, or the grantee's notification of termination. The normative juridical approach is utilised for the research. Since the Absolute Power of Attorney deed fails to fulfil the objective requirements according to Article 1320 of the Civil Code, as regulated in the Minister of Home Affairs Instruction No. 14 of 1982, the author argues that it cannot be used to transfer land rights and is thus null and void by law. Government Regulation No. 24 of 1997, Article 39, Paragraph 1, Letter d, forbids the use of absolute power of attorney to transfer land rights; this regulation is still frequently cited even though the instruction is no longer in effect.